Authorship characteristics of retracted COVID-19 articles - Rafaela Carolina da Silva (Faculdade de Medicina do ABC, 2021)
Following the explosion of publications about COVID-19, some of these articles were retracted. These articles are potentially dangerous to public health as they can mislead about the nature of the virus. The growth and sensitive nature of retracted papers led to bibliometrics studies on them, although few, which focused more on the level of documents. This study, instead, examines the characteristics of the authors of these articles. 54 retracted COVID-19 articles that fit our study’s criteria were identified. The results revealed that 32% of these authors were MD, and about one-fifth of them had a past history of publishing retracted articles. The average number of authors per article was 6. Also, according to their profile in the Scopus, the mean number of documents, citations and their H-index were 61, 3159 and 12, respectively. Women also appeared in one-third of the articles as first and last authors. Continued research about retracted COVID-19 articles can continue to help prevent the further dissemination of questionable research findings.